2017
DOI: 10.3389/fimmu.2017.00579
|View full text |Cite
|
Sign up to set email alerts
|

GRP78 Impairs Production of Lipopolysaccharide-Induced Cytokines by Interaction with CD14

Abstract: The 78-kDa glucose-regulated protein (GRP78) is a stress-inducible chaperone that resides primarily in the endoplasmic reticulum. GRP78 has been described to be released at times of cellular stress and as having extracellular properties that are anti-inflammatory or favor the resolution of inflammation. In the current study, we confirmed that GRP78 impaired the production of lipopolysaccharide-induced pro-inflammatory cytokines in GRP78-treated bone-marrow-derived dendritic cells (DCs). To explore the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 47 publications
(76 reference statements)
1
27
1
Order By: Relevance
“…GRP78 was highly expressed in the liver, suggesting a potential role in reshaping the hepatic microenvironment to facilitate liver metastasis. sGRP78 has been implicated in immunomodulation by biding to pattern recognition receptors ( 9 , 18 ). Moreover, intracellular GRP78 levels have been associated with drug resistance and apoptosis in cancers ( 11 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GRP78 was highly expressed in the liver, suggesting a potential role in reshaping the hepatic microenvironment to facilitate liver metastasis. sGRP78 has been implicated in immunomodulation by biding to pattern recognition receptors ( 9 , 18 ). Moreover, intracellular GRP78 levels have been associated with drug resistance and apoptosis in cancers ( 11 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…GRP78 is upregulated during ER stress; GRP78 translocates from the ER to the cell membrane (mGRP78) or is secreted as soluble GRP78 (sGRP78) ( 8 ). sGRP78 has long been recognized as a resolution-associated molecular pattern, facilitating inflammation resolution ( 9 11 ). GRP78 is expressed at higher levels in cancer tissues than in adjacent healthy tissues, and its expression levels have been associated with tumor malignancy ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other previous studies have shown that GRPs are negative regulators of inflammatory processes. GRP78 has been shown to inhibit the production of pro-inflammatory cytokines (TNF-α, IL-6 and IFN-β) induced by lipopolysaccharide (LPS) in bone marrow-derived dendritic cells (BMDCs) and bone-marrow-derived macrophages (BMDMs) [ 64 ]. Additionally, transient knockdown of GRP78 has been shown to abolish the secretion of serum ferritin mediated pro-inflammatory cytokines (IL-1β, IL-6 and TNF-α) in rat primary activated hepatic stellate cells [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pool of extracellular CD14 in vivo, known as soluble CD14, is detected in different fluids during infection and particularly during sepsis, a life-threating condition resulting from exacerbated inflammation in response to infection (Barratt-Due et al, 2017;Bas et al, 2004). Extracellular CD14 during microbial infection is important for host defense, in particular for bacterial clearance, but little is known about the release of CD14 in vivo (Fang et al, 2017;Knapp et al, 2006;Sahay et al, 2018;Wieland et al, 2005).…”
Section: Introductionmentioning
confidence: 99%